2020
DOI: 10.1002/csc2.20018
|View full text |Cite
|
Sign up to set email alerts
|

High‐density SNP‐based genetic diversity and heterotic patterns of tropical maize breeding lines

Abstract: Understanding the crop diversity is critical for a successful breeding program, helping to dissect the genetic relationship among lines, and to identify superior parents. This study aimed to investigate the genetic diversity of maize (Zea mays L.) inbred lines and to verify the relationship between genetic diversity and heterotic patterns based on hybrid yield performance. A total of 1,041 maize inbred lines were genotyped-by-sequencing, generating 32,840 quality-filtered single nucleotide polymorphisms (SNPs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 36 publications
3
16
1
Order By: Relevance
“…Generally, high PIC values indicate the effectiveness of markers for linkage analysis when estimating the inheritance between parental lines and the derived hybrids [41], whereas the GD or expected heterozygosity (He) reveals gene diversity for haploid markers and gives information on the proportion of the genetic distance and average heterozygosity within a given population [41,42]. In the present study, an average PIC of 0.25 was obtained, which is comparable to that reported earlier by Dao et al [27] and Zhang et al [28], as well as the 0.24 of Yu et al [43] and 0.29 of Wu et al [44], but higher compared with the results of Adu-Boakyewaa et al [15] and Silva et al [45] who reported average PIC values of 0.19 and 0.17, respectively. The high mean PIC value observed implied that majority of the selected SNPs were informative and polymorphic enough to bring out the differences among the 162 inbred lines studied.…”
Section: Discussionsupporting
confidence: 88%
“…Generally, high PIC values indicate the effectiveness of markers for linkage analysis when estimating the inheritance between parental lines and the derived hybrids [41], whereas the GD or expected heterozygosity (He) reveals gene diversity for haploid markers and gives information on the proportion of the genetic distance and average heterozygosity within a given population [41,42]. In the present study, an average PIC of 0.25 was obtained, which is comparable to that reported earlier by Dao et al [27] and Zhang et al [28], as well as the 0.24 of Yu et al [43] and 0.29 of Wu et al [44], but higher compared with the results of Adu-Boakyewaa et al [15] and Silva et al [45] who reported average PIC values of 0.19 and 0.17, respectively. The high mean PIC value observed implied that majority of the selected SNPs were informative and polymorphic enough to bring out the differences among the 162 inbred lines studied.…”
Section: Discussionsupporting
confidence: 88%
“…On average, there were 525 SNPs in each chromosome, ranging from 327 in chromosome 10 to 926 in chromosome 1 (Figure 1A). This distribution of SNPs throughout the genome was similar to other studies in maize using this type of marker (Li et al 2018, Guo et al 2019, Leng et al 2019, Silva et al 2020. Unlike primary molecular marker systems, high-density marker genotyping allows simultaneous analysis of markers widely distributed throughout the genome.…”
Section: Resultssupporting
confidence: 84%
“…Furthermore, genetic diversity studies are commonly carried out in maize breeding programs in an effort to classify lines into heterotic groups (Wu et al 2016, Leng et al 2019, Silva et al 2020 because parents with high per se performance and genetic divergence from each other are important requirements for manifestation of heterosis (Prasad and Singh 1986). Classification of inbreds into heterotic groups using information on genetic diversity facilitates directed crosses between inbreds from contrasting groups and reduces the number of hybrid crosses made in a breeding program, thus increasing the efficiency of the program and leading to accelerated genetic gains from selection (Reif et al 2005).…”
Section: Ls Oliveira Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The maize diversity panel was comprised two hundred and ve maize inbred lines, from the breeding program of Embrapa (Brazilian Agricultural Research Corporation) Maize and Sorghum, located in Sete Lagoas, state of Minas Gerais, Brazil (Silva et al 2019). During the 2014/2015 crop season, the 205 lines were evaluated in three eld trials conducted in the experimental station of Embrapa Mid-North, located in Teresina, state of Piauí, Brazil.…”
Section: Genotypes and Experimental Designmentioning
confidence: 99%